Answer:
the answer is the letter a) -sin x
Step-by-step explanation:
Simplify the expression.
sine of x to the second power minus one divided by cosine of negative x
(1−sin2(x))/(sin(x)−csc(x))
sin2x+cos2x=11−sin2x=cos2x
cos2(x)/(sin(x)−csc(x))csc(x)=1/sin(x)cos2(x)/(sin(x)− 1/sin(x))= cos2(x)/((sin2(x)− 1)/sin(x))sin2(x)− 1=-cos2(x)cos2(x)/(( -cos2(x))/sin(x))
=-sin(x)
Answer:
Step-by-step explanation:
there is a 50/50 chance of getting a chocolate cupcake. :P
<span>The cosine of an angle is the quotient of the side that angle lay on and the hypotenuse.</span>
x-hypotenuse
cos45=19/x
0.707=19/x, x=19/0.707, x=26.9
Hypotenuse is <span>approximately 27.</span>
Is this for a quiz? It looks familiar
When x = 1:
1³ + 1 - 3 = -1
When x = 2:
2³ + 2 - 3 = 7
Since f(x) = x³ + x - 3 is continuous, it follows from the intermediate value theorem that for some c in the interval (1, 2), we have f(c) = 0, since f(1) < 0 < f(2).